Breadth of knowledge vs. grades: What best predicts achievement in the first year of health sciences programmes? - Shulruf, Boaz; Li, Meisong; McKimm, Judy; Smith, Melinda (Journal of Educational Evaluation for Health Professions, 2012)
This study aimed to identify those features within secondary school curricula and assessment, particularly science subjects that best predict academic achievement in the first year of three different three-year undergraduate health professional programmes (nursing, pharmacy, and health sciences) at a large New Zealand university. In particular, this study compared the contribution of breadth of knowledge (number of credits acquired) versus grade level (grade point average) and explored the impact of demographic variables on achievement. The findings indicated that grades are the most important factor predicting student success in the first year of university. Although taking biology and physics at secondary school has some impact on university first year achievement, the effect is relatively minor.